Caso Clínico ARP Nº17: Arterite de Takayasu - Ferreira, Margarida (2021)
39 year old female, presenting at ER with aphasia and right hemiparesis. A few hours later, develops mild hemoptysis. Thoracic CT performed to exclude pulmonary embolism. Patient taking immunosupressants for suspected demyelinating disease (multiple sclerosis?), due to relapsing-remitting but progressive episodes of limb weakness and numbness and impaired and blurred vision.